Coronary Artery Aneurysm after Second-Generation Drug-Eluting Stent Implantation - Hong, Sung-Jin; Kim, Hyoeun; Ahn, Chul-Min; Kim, Jung-Sun; Kim, Byeong-Keuk; Ko, Young-Guk; Hong, Bum-Kee; Choi, Donghoon; Jang, Yangsoo; Hong, Myeong-Ki (Yonsei medical journal, 2019)
We evaluated the incidence, predictors, and prognosis of coronary artery aneurysm (CAA) after second-generation drug-eluting stent (DES) implantation. A total of 976 consecutive patients (1245 lesions) who underwent follow-up angiography after second-generation DES implantation were analyzed. Incidence and predictors of CAA were assessed, and clinical prognosis was compared with 34 cases of CAA after first-generation DES implantation using previous CAA registry data. All 10 cases of CAA (0.80% per lesion) in 10 patients (1.02% per patient) were detected at follow up. Compared to lesions without CAA, those with CAA had greater involvement of the proximal segment (90% vs. 51%, =0.014), a higher proportion of pre-intervention, a Thrombolysis in Myocardial Infarction score of 0 or 1 flow (80% vs. 16%, <0.001), more chronic total occlusions (40% vs. 10%, <0.001), and longer implanted stents (41.9±23.2 mm vs. 28.8±14.8 mm, =0.006). As for CAA morphology, instances of CAA after second-generation DES were predominantly the single fusiform type (90%), whereas instances of CAA after first-generation DES were multiple saccular (47%) and single saccular (35%) types ( <0.001). Myocardial infarction with stent thrombosis occurred in 5 patients with CAA after first-generation DES (15%), and no adverse events were observed in patients with CAA after second-generation DES over a median follow-up duration of 4.3 years ( =0.047, log-rank). Although CAAs after second-generation DES implantation were detected at a similar incidence to that for CAAs after first-generation DES implantation, second-generation DES-related CAAs had different morphologies and more benign clinical outcomes versus first-generation DES-related CAAs.